Prevalence of behaviour-related fertility disorders in a clinical sample: results of a pilot study - Schilling, Kathrin; Toth, Bettina; Rösner, Sabine; Strowitzki, Thomas; Wischmann, Tewes (Archives of gynecology and obstetrics, 2012)
Introduction: There is no doubt that lifestyle factors can be detrimental to fertility. The aim of the present pilot study was to identify initial prevalence rates for behaviour-related fertility disorders in a clinical sample of couples wanting a child.MethodsBetween February 2010 and August 2010, all patients coming for the first time to Heidelberg University’s Women’s Hospital for consultation on involuntary childlessness were asked to fill out a questionnaire designed by the authors of this article. The questionnaire was based on a review of the relevant literature, with special reference to the latest research findings on behaviour detrimental to fertility. Of the 156 couples addressed, 110 women and 100 men took part in the study.ResultsFor behaviour-related infertility, 9 % of the women and 3 % of the men in our sample were classified on the basis of BMI <18.5, sexual disorders, or abuse of anabolic steroids. If we include smokers, these figures increase: 11 % female smokers and 18 % male smokers. A further 19 % of the women practised sport to an excessive degree; and 26 % of the women and 53 % of the men had a BMI ≥25.DiscussionThe prevalence of behaviour-related fertility disorders should not be underestimated. For the prevention of behaviour-related fertility disorders, it is important to inform the population about lifestyle-mediated fertility risks.
Gesehen am 07.05.2018